(untitled) (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2025)
This study examines the linguistic and rhetorical strategies employed by President Tinubu in his 1st October 2024 Independence Day Speech and how it has helped in shaping public perception and national identity. Using Fairclough’s three-dimensional model of discourse analysis, textual analysis, discursive practice, and social practice, and Leech and Short’s framework which focuses on analysing literary devices by examining how they are used to convey meaning, and understand speaker’s intent, this research explores the power dynamics, ideological underpinnings, and persuasive elements used in the speech. The study also investigates how Tinubu’s language choices reflect power dynamics, governance priorities, and efforts to foster national unity. The study uses a qualitative research approach and the methodology involves several steps to systematically analyse the speech and identify the rhetorical devices used by the president in his Independence Day speech. The findings of the study reveal that President Tinubu employed a range of rhetorical devices in his speech, including metaphors, personifications, hyperboles, parallelisms, similes, antitheses, anaphora among others. These rhetorical elements employed in the speech are used by the president to establish trust, inspire hope, outline policy priorities, and promote national unity.